Aerobic Bacterial Flora In The False Vampire Bat Megaderma Lyra (Journal of Pharmaceutical Negative Results, 2023)
Bats play an important ecological role all over the world, and their presence is thought to be an indicator of a healthy ecosystem. Microorganisms play an important role in maintaining the delicate ecological balance of the earth. But frequently, they have a negative public image as a vector of disease-causing microbes. Megaderma lyra, a common carnivorous bat, was chosen to study the impact of their microbial flora. The oral cavity and intestinal bacterial florawas collected. Nutrient agar, Blood agar, MacConkeyagar, and Salmonella shigella agar culture medium were prepared to identify the aerobic organisms. Bacterial species isolated from M.lyra harboured twelve species belonging to three different families; ten from Enterobacteriaceae, one from Streptococcaceae and one from Pseudomonadaceae. Studies on the oral aerobic flora of this bat species revealed, that they have the same microbial flora as any mammal, including humans. Dietary items of carnivorous bats are also a major influencing factor on bacterial oral cavity bacterial floral composition. This work made an attempt of focus the bacterial flora of M.lyra.